Fixed Bed Adsorption Of Carbon Dioxide On Modified Coconut Shell Granular Activated Carbon - Tan, Yee Ling (2014)

(untitled)
Chemically modified adsorbent is attracting attention on its ability in carbon dioxide capture in order to increase the adsorption capacity and enhance its characteristics such as thermal and chemical resistance. In this research, a series of chemically modified coconut shell granular activated carbon were prepared, characterized and used in CO2 adsorption process in a fixed-bed adsorption system. Penjerap diubahsuai secara kimia telah menarik perhatian atas keupayaannya menangkap karbon dioksida untuk meningkatkan kapasiti penjerapan dan ciri-cirinya seperti rintangan haba dan kimia. Dalam kajian ini, satu siri karbon teraktif tempurung kelapa terubahsuai telah disediakan, dicirikan dan digunakan dalam proses penjerapan CO2 dalam sistem penjerapan lapisan tetap.